Extracellular Signal-Regulated Kinase in the Basolateral Amygdala, but not the Nucleus Accumbens Core, is Critical for Context-Response-Cocaine Memory Reconsolidation in Rats - Wells, Audrey M (Nature Publishing Group, 2013)
The reconsolidation of cocaine memories following retrieval is necessary for the sustained ability of a cocaine-paired environmental context to elicit cocaine seeking. Extracellular signal-regulated kinase (ERK) is an intracellular signaling molecule involved in nucleus accumbens core (NACc)-mediated reconsolidation of Pavlovian cocaine memories. Here, we used a rodent model of drug context-elicited relapse to test the hypothesis that ERK would be similarly required for the reconsolidation of context-response-cocaine memories that underlie drug context-induced reinstatement of instrumental cocaine-seeking behavior, with a focus on the NACc and on the basolateral amygdala (BLA), another important locus for the reconsolidation of cocaine memories. We show that the mitogen-activated protein kinase (MEK)/ERK1/2 inhibitor, U0126 (1.0 μg/0.5 μl/hemisphere), microinfused bilaterally into the BLA—but not the NACc—immediately after brief re-exposure to a previously cocaine-paired context (that is, cocaine-memory reactivation), significantly attenuated subsequent drug context-induced cocaine seeking relative to vehicle (VEH). This effect in the BLA was associated with a transient inhibition of ERK1/2 phosphorylation, and it depended on memory reactivation given that U0126 administered following exposure to a novel context did not alter subsequent cocaine seeking. Furthermore, similar to U0126, baclofen+muscimol-induced (B+M; 106.8/5.7 ng/0.5 μl/hemisphere) neural inactivation of the NACc, following cocaine-memory reactivation, failed to alter subsequent cocaine seeking. These findings demonstrate that ERK activation in the BLA, but not the NACc, is required for the reconsolidation of context-response-cocaine associative memories. Together with prior research, these results suggest that contextual drug-memory reconsolidation in Pavlovian and instrumental settings involves distinct neuroanatomical mechanisms.